¿Son la potestad suprema y la independencia notas intrínsecas a la república en Vitoria y Suárez? - Castaño, Sergio Raul (2013)
The article deals with the position of Francisco de Vitoria and Francisco Suárez concerning the political power as superiorem non recognoscens. The author?s aims are to prove that that principle belongs in fact to their political philosophy, and to understand the sense and foundations of their political independence's notion.